Spike-field coherence in the low-gamma band of the primary visual cortex of agouti and cats - Moura, Júlio Cesar da Costa (2021)
Neural oscillations in the low gamma band (30-49 Hz) have been related to visual processing. Spike-field coherence is an established measure to study neural synchronicity and communication between two neural sources but can also be applied to study the coordination of spiking activity and the local field potential (LFP) as a signature of functional cortical layout and local connectivity. Along the same line, the phase-locking value (PLV) is used to study oscillatory activity between LFP and spiking activity. It was observed previously, that the spike-field responses in the primary visual cortex (V1) of cats are phase locked in the low gamma band and are tuned to the same orientation as the spike rate. Importantly, the orientation-selective neurons of cats are organized in periodic columns arranged in pinwheel-like structures. Therefore, the interpretation that the strong and tuned interactions between spikes and LFPs of the same electrode could reflect that orderly columnar layout when stimulating with salient oriented visual stimuli, stands to reason. All rodents investigated so far – including the large visual rodent agouti - possess orientation-selective neurons and evoke robust responses to moving oriented sinusoidal gratings. However, they do not express regular maps as cats or primates, but, if at all, mini-columns interspersed with “salt-and-pepper” regions. Although agouti neurons occasionally exhibit oscillatory spiking and LFP activity in the low gamma range this activity is almost never tuned to the same orientation as the spike rate confirming the hypothesis that a columnar layout facilitates the occurrence of tuned oscillations. In the present thesis, we aimed to further elucidate the role of gratings in driving the tuned coherent gamma oscillations in visual cortices with a columnar versus a non-columnar layout. Therefore, we compared spiking and LFP activity in cat and agouti primary visual cortex evoked by three different whole-field stimuli of different spatial coherence, containing either strong, moderate or no orientation component, namely gratings, textures of randomly placed oriented bars (RBT) and random-dot textures (RDT). In detail, we examined whether mean firing rate, Fano factor (FF), spike-field coherences and frequencies, cross-spectrum of oscillation and frequencies, (PLV) and orientation selectivity index (OSI) evoked by the three different stimulus types vary in a species-specific manner, which could be explained by the supposedly different functional layouts. To this end, we have analyzed the metrics for multi unit activity-LFP (MUA-LFP) and single unit activity-LFP (SUA-LFP) in visual evoked potential and sustained phase windows in which index (OSI) > 0.1, mean firing rate > 2.00 spikes/secs and mean firing rate < 200.00 spikes/secs. Overall, firing rates, OSI, spike-field coherence and oscillation frequencies tend to be higher in cats than in agoutis for all stimulus types. We observed significant differences of raw spike-field coherence in the low gamma band between species for all three stimuli (p-Value of Mann–Whitney U test < 0.0001 for all stimuli in both MUA-LFP and SUA-LFP) during the sustained phase window (MUA-LFP – Agouti: grating: n=143; RBT: n=139; RDT: n=104; Cat: grating: n=399; RBT: n=351; RDT: n=200; SUA-LFP – Agouti: grating: n=226; RBT: n=221; RDT: n=176; Cat: grating: n=532; RBT: n=365; RDT: n=230). We observed the same result for spikefield coherence frequencies (p-Value of Mann–Whitney U test < 0.0001 for all stimuli in MUA-LFP and SUA-LFP). Gratings seem to be more efficient than RDT or RBT textures in evoking high spike-field coherences in both species. This tendency is only significant in cats. Although agoutis follow that tendency, especially in the sustained response, the majority of metrics do not show any significant difference between the three stimuli. Our results indicate that visually evoked neuronal activity in cats exhibits more robust spike-field coherence than in agoutis. Both layout types, columnar and interspersed, can express coherent low gamma oscillatory activity especially when challenged with optimally oriented gratings.